Strategic Human Resource Planning in the Era of Digital Transformation - Adiazmil. S., Aan; Hidayat, Muhammad; Basuil, Dynah A. (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Digital transformation has had a significant impact on business and human resource management (HR). This research explores "Strategic Human Resource Planning in the Era of Digital Transformation" through a systematic literature review. Key findings include deep technology integration, key stakeholder engagement, and an emphasis on developing employee skills and leadership as crucial elements in responsive HR planning. Organizations that successfully align HR planning with sustainable development goals also create broader positive impacts. Nonetheless, implementation challenges such as change resistance, technological uncertainty, and difficulty in predicting skills needs are a major focus. In conclusion, this research provides in-depth insights, highlights knowledge gaps, and details future research opportunities to help organizations navigate the changing dynamics of the digital era.